(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The literature does not yet explicitly explain practical flexibility, despite its strategic relevance. Empirical investigations have reached different and often opposing findings based on several concepts and measurement methodologies. This study proposes a structure to define and measure functional flexibility in the field of human resource management. By classifying previous definitions as well as causative in the process, we will try to understand this word. In the first part of this essay we examine and argue the necessity for some practical flexibility in the administration of human resources operations, which helps the company adjust to changing environments. From this point of view, this talent is seen as an important source of competitive advantage. In order to expand more detailed research in this area, we propose a new functional versatility framework and measure model, based on our theoretical analysis. This design should be used as a basis for constructing a realistic scale for the evaluation of versatility. A possible path of study arising from this examination is mentioned in the concluding section of the report. We concentrate on examining how the development and utilisation of human resources is incorporated into flexible organising strategies for human reserves.